Stripping voltammetric determination of platinum metals at a carbon paste electrode modified with cationic surfactants - Svancara, Ivan; Galík, Michal; Vytras, Karel (Talanta, 2007)
In this contribution, a novel method is described for the determination of platinum metals. The procedure developed employs a carbon paste electrode modified in situ with cationic surfactants of the quaternary ammonium salt type. The pre-concentration step is based on a specific accumulation mechanism involving ion-pair formation; the detection being performed by cathodic scanning in the differential pulse voltammetric mode. Regarding the individual forms of platinum metals, the method has been found convenient for the determination of three heavy platinum metals in the form of Pt(IV), Ir(III) and Os(IV), whereas for the remaining elements (Ru, Rh, and Pd) was almost inapplicable. Platinum metals of the former group can be pre-concentrated in chloride-containing supporting media via PtCl(6)(2-), IrCl(6)(3-) and OsCl(6)(2-) complex anions, the central atom of each species being fairly reducible during the voltammetric scan. Stripping signals for both platinum and iridium were proportional to the concentration in a range of 1-10x10(-6)M Pt(IV) and Ir(III); the response for osmium being linear within 0.1-6x10(-7)M Os(IV) with a detection limit of about 5x10(-9)moll(-1). During optimisation, special attention was paid to the accumulation mechanism, choice of key experimental conditions, and to interference effects from foreign ions with potentially ion-pairing capabilities (AuCl(4)(-), TlCl(4)(-), CrO(4)(2-), MnO(4)(-), SCN(-), and I(-)). The method elaborated has been tested on both model solutions and real samples of industrial waste water, showing in both cases satisfactory analytical performance.